Love on the rocks : men, women, and alcohol in post-World War II America - Rotskoff, Lori (Gender & American culture., 2002)
Alcohol has always had a special role in the United States. From 1620, when the Puritans were forced to land on Plymouth Rock because the Mayflower had almost run out of beer, until 1933, when Prohibition was repealed in an unprecedented move, the use of alcohol has been the baton by which the self-righteous have conducted antipleasure movements in America. In her well-researched, well-written book, Lori Rotskoff shows how the drinking of alcohol assumed another role: "workers forged a sense of class identity during their leisure hours ... passed in the familiar surroundings of the neighborh